Textual Syntactic Complexity and Its Role In Second Language Reading Outcomes In Indonesia - Sahiruddin (JEELS (Journal of English Education and Linguistics Studies), 2019)
This paper examines the role of syntactic complexity in L2 reading outcomes across different EFL proficiency levels in an Indonesian university. Indonesian university students (N = 148) at Intermediate and Advanced levels of proficiency read four English passages differing in syntactic complexity. The latter was measured by several widely used text modelling tools. Participants read two low and two high complexity texts and completed a post-test comprehension test. Syntactic complexity had a statistically significant but low magnitude effect size, accounting for 2%-5% of the variance of reading performance between the L2 English proficiency levels. There were also noticeable differences in text analysis measures across the different complexity tools. The usefulness of syntactic complexity as an isolated dimension of text complexity is evaluated. The contribution of this study to the field both in theory and practice is presented.